Intravenous neutralization of vascular endothelial growth factor reduces vascular function/permeability of the ovary and prevents development of OHSS-like symptoms in rhesus monkeys - C. V. Bishop; D. M. Lee; O. D. Slayden; X. Li (BMC, 2017)
Abstract Background Ovarian hyperstimulation syndrome (OHSS) is a disorder associated with elevated serum VEGFA following chorionic gonadotropin (hCG) exposure in controlled ovarian stimulation (COS) cycles in women. In this study, we tested the effect of intravenous VEGFA neutralization on OHSS-like symptoms and vascular function in rhesus macaques during COS cycles. Methods Monkeys (n = 8) were treated with 3 COS protocols and assigned randomly to groups as follows: 1) COS alone (Control, n = 5); 2) COS + VEGF mAb Avastin 19 ± 5 h before hCG (Avastin pre-hCG; n = 6); 3) COS + Avastin 3-4 days post-hCG (Avastin post-hCG; n = 4); 4) COS + Simulated Early Pregnancy (SEP n = 3); or 5) COS + SEP + Avastin (SEP + Avastin n = 3). Follicles were aspirated 36 h post-hCG, fluid was collected from one follicle for analysis of steroid and vascular hormone content. Remaining follicles were aspirated, and luteinized granulosa cells (LGCs) cultured for 24 h. Ovarian/uterine vascular flow (VF) and blood volume (BV) were analyzed by contrast enhanced ultrasound (CEUS) before hCG bolus and 6-8 days post-hCG bolus/time of peak SEP response. Ovarian permeability to albumin was analyzed by Dynamic Contrast Enhanced-MRI (DCE-MRI) post-hCG. Results Abdominal fluid was present in 4/5 Control, 2/6 Avastin pre-hCG, and 3/4 Avastin post-hCG females. Neutralization of VEGFA before hCG reduced ovarian VF, BV, and permeability to albumin (P < 0.05), while only ovarian VF and permeability were reduced in Avastin-post hCG group (P < 0.05). There was no effect of Avastin on ovarian vascular function during COS + SEP. VEGF levels in follicular fluid were reduced 78-fold by Avastin pre-hCG, and LGCs exposed to Avastin in vivo also released 4-fold less VEGF into culture media (P < 0.05). Culture medium of LGCs exposed to VEGFA neutralization in vivo had lower levels of P4 and ANGPT1, and an increased ratio of ANGPT2/1 (P < 0.05). Uterine VF was reduced by SEP + Avastin in the basalis/junctional zone (P < 0.05). Conclusions Avastin treatment before hCG prevents the development of symptoms associated with ovarian hyperstimulation syndrome. In vitro data suggest neutralization of VEGFA alters expression of other vascular factors typically induced by hCG in the luteinizing follicle. Neutralization of VEGFA action alters the vascular function of the basalis zone of the uterus during simulated early pregnancy, indicating a potential effect on embryo implantation.